The basis of traditional Chinese medicine - Shen, Ziyin; Chen, Zelin (Boston : Shambhala, 1996)
Een aangename kennismaking met de traditionele Chinese geneeskunst: Yin-yang, traditionele Chinese kruiden, acupuntuur, ...
Originally published: Hong Kong : Commercial Press, c1994.
Keywords: Medicine, Chinese